2015
DOI: 10.1080/19491034.2015.1059546
|View full text |Cite
|
Sign up to set email alerts
|

Linking dosage compensation and X chromosome nuclear organization inC. elegans

Abstract: A nimal sex is determined by the number of X chromosomes in many species, creating unequal gene dosage (aneuploidy) between sexes. Dosage Compensation mechanisms equalize this dosage difference by regulating X-linked gene expression. In the nematode C. elegans the current model suggests that DC is achieved by a 2-fold transcriptional downregulation in hermaphrodites mediated by the Dosage Compensation Complex (DCC), which restricts access to RNA Polymerase II by an unknown mechanism. Taking a nuclear organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…First, the nuclear positioning model predicts that in males the transgenes on X should have elevated expression relative to transgenes on autosomes due to a rex -dependent association of X with the nuclear periphery. However, we found that in males, expression of single-copy transgenes on the sole X chromosome was not different from expression of single-copy transgenes inserted on only one of two homologous autosomes ( Figure 6C ), contrary to the nuclear positioning model of dosage compensation ( Sharma et al, 2014 ; Sharma and Meister, 2015 ).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…First, the nuclear positioning model predicts that in males the transgenes on X should have elevated expression relative to transgenes on autosomes due to a rex -dependent association of X with the nuclear periphery. However, we found that in males, expression of single-copy transgenes on the sole X chromosome was not different from expression of single-copy transgenes inserted on only one of two homologous autosomes ( Figure 6C ), contrary to the nuclear positioning model of dosage compensation ( Sharma et al, 2014 ; Sharma and Meister, 2015 ).…”
Section: Resultsmentioning
confidence: 75%
“…Our analysis of X-chromosome regulation enabled us to evaluate an attractive but speculative model of X-chromosome dosage compensation, which posits that repression of X-linked gene expression in XX animals by the DCC is merely the result of escaping from a chromosome-wide mechanism that upregulates X expression ( Sharma et al, 2014 ; Sharma and Meister, 2015 ). In particular, these authors proposed that rex sites target X to the nuclear periphery in males to increase chromosome-wide gene expression, while DCC binding to rex sites in hermaphrodites blocks the peripheral localization, relocating X to the interior and hence reducing X gene expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors involved in location of the active X, which is often located near the nuclear membrane in mammals, remain to be determined. In Drosophila and C. elegans , nuclear pore complexes associate with the active X chromosome, consistent with a specific nuclear location [125, 126]. …”
Section: Molecular Evidence Of X Upregulationmentioning
confidence: 99%
“…In males, the X chromosome interacts with nucleoporins, creating an activating compartment able to increase X-linked genes expression. In hermaphrodites, DCC loading onto X chromatin on the one hand increases overall chromosome compaction and TAD structure while on the other hand it impairs activation at pores by masking the interaction sites and altering X chromosome position [53,59]. How these changes ultimately impact RNA polymerase levels on the X remains to be elucidated.…”
Section: Nematodes: Sex-specific Nuclear Compartments To Fine-tune Trmentioning
confidence: 99%